ASUHAN KEBIDANAN BERKELANJUTAN PADA NY. B, NY. L, NY. R DI PMB FARIDA SORAYA, SST TELUK BETUNG BANDAR LAMPUNG TAHUN 2022 - Puspa Aria Ningrum; Komalasari (CV. Multi Kreasi Media, 2023)
Nearly all maternal deaths occur in developing countries, with more than half occurring in SubSaharan Africa and almost one third occurring in South Asia. This is still in the high category because it has not reached the Sustainable Development Goals (SDG's) target of <70 per 100,000 live births (WHO, 2018). The government's efforts to reduce the Maternal Mortality Rate (MMR) are by implementing elements of health services including pregnancy monitoring, improving pregnant nutrition, implementing family planning (KB) programs, maternal immunization and improving the referral system (Manuaba, 2012). Another way that can be done is by using continuous health efforts or Continuity Of Care (COC) with the aim of improving the quality of services that require continuous relationships between patients and health professionals. Able to perform comprehensive and continuous midwifery care supported by the ability to think critically, clinical and reflective rationalization in pregnancy, childbirth, postpartum, and BBL as well as providing infant massage therapy interventions on the frequency of breastfeeding babies at BPM Farida Soraya, SST, Teluk Betung Bandar Lampung Year 2022. In this final project report, the authors use a midwifery care approach that focuses on midwifery care in pregnancy, childbirth, the postpartum period, BBL and family planning overall midwifery care and collaborative infant massage to increase the frequency of breastfeeding in infants. In this midwifery care, the subject of care is the mother who carries out the examination from pregnancy to carrying out family planning program plans and conducting infant massage interventions. The study conducted on Mrs. B, Mrs. R and Mrs. L with pregnancy after being given midwifery care, the mother said she would prepare for the delivery later. Delivery care resulted in Mrs. B, Ny. R and Ny.L did well and smoothly. After conducting a subjective data review, By.Ny.B, By. Mrs. L and By. Mrs. R experienced problems with the frequency of breastfeeding because she was reluctant to breastfeed, so massage was done to increase the frequency of breastfeeding with the result that after being given a massage the baby was able to breastfeed approximately 8-9 times a day. After conducting an assessment of objective data, a problem was found, namely the duration of breastfeeding the baby so that the baby massage technique was carried out. The diagnosis made in this case was normal delivery and normal postpartum care for Mrs. B, Mrs. L and Mrs. R.